CIPTA LAGU ANAK WARNA WARNI SEBAGAI MEDIA EDUKASI ESTETIKA DAN APRESIASI ALAM UNTUK USIA DINI - Nur Indriani; Anisa Safitri; Ameliya; Irmalasari; Nurdamayanti; Khusnal Hawa Tiwi; Ftri Hijratunnisah; Wuwun; Abdul Afan Gafar; Roy Martin; Irmaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the decreasing number of children's songs with educational and aesthetic value, while young children are more familiar with popular adult songs that are less relevant to their world. This condition creates a need for musical works that can foster sensitivity, appreciation of nature, and aesthetic values ​​from an early age. The purpose of this research is to create a children's song entitled